Use of Perfusion Imaging and Other Imaging Techniques to Assess Risks/Benefits of Acute Stroke Interventions - Tarpley, Jason (2013)
The advent of multimodal neuroimaging has provided acute stroke care providers with an armamentarium of sophisticated imaging options to utilize for guidance in clinical decision-making and management of acute ischemic stroke patients. Here, we propose a framework and potential algorithm-based methodology for imaging modality selection and utilization for the purpose of achieving optimal stroke clinical care. We first review imaging options that may best inform decision-making regarding revascularization eligibility, with a focus on the imaging modalities that best identify critical inclusion and exclusion criteria. Next, we review imaging methods that may guide the successful achievement of revascularization once it has been deemed desirable and feasible. Further, we review imaging modalities that may best assist in both the non-interventional care of acute stroke as well as the identification of stroke-mimics. Finally, we review imaging techniques under current investigation that show promise to improve future acute stroke management.